Feline discrete high‐grade gastrointestinal lymphoma treated with surgical resection and adjuvant CHOP‐based chemotherapy: retrospective study of 20 cases. (3rd September 2015) - Gouldin, E. D.; Mullin, C.; Morges, M.; Mehler, S. J.; de Lorimier, L.‐P.; Oakley, C.; Risbon, R.; May, L.; Kahn, S. A.; Clifford, C.
Abstract: The aim of this retrospective study was to evaluate the outcome of cats treated with surgical intervention for a discrete intermediate‐/high‐grade gastrointestinal lymphoma prior to CHOP‐based chemotherapy. Variables including sex, breed, haematocrit, white blood cell count, serum albumin concentration, clinical stage of disease, gastrointestinal obstruction and peritonitis were assessed for their effect on survival. Twenty cats met the inclusion criteria with three cats still alive at the time of data analysis. The overall median survival time (MST) was 417 days (range: 12–2962 days). The disease‐free interval (DFI) was 357 days (range: 0–1585 days) with six cats still deemed in remission prior to death. Only clinical stage had a significant effect on both MST and DFI. Cats with discrete intermediate/high‐grade gastrointestinal lymphoma that undergo surgical resection followed by adjuvant CHOP chemotherapy may achieve acceptable overall survival times.